Stock Status Assessments of Five Small Pelagic Species in the Atlantic and Pacific Oceans Using the Length-Based Bayesian Estimation (LBB) Method - Kindong, Richard; Gao, Chunxia; Pandong, Njomoue Achille; Ma, Qiuyun; Tian, Siquan; Wu, Feng; Sarr, Ousmane (Frontiers in Marine Science, 2020)
A rising trend in catches of non-targeted species have recently been observed in major fisheries including tuna longline fisheries, yet most of these species are unmanaged. Given their importance to local economies and sustainable livelihoods in many coastal countries, there is a need to provide plans for their management. However, most non-targeted species are data-limited which hampers the use of conventional assessment methods. This study applied a novel length-based Bayesian biomass estimator (LBB) method to five species from the Atlantic and Pacific Oceans. Estimates of growth, length at first capture and present relative biomass (B/B0, B/BMSY) of these species were gotten from length-frequency (LF) data. Of the ten populations (5 species from 2 regions) assessed, one has collapsed, one grossly overfished, and three overfished. Six populations had the ratio of mean lengths at first capture (Lc) on the mean length at first capture, which maximizes the catch and biomass (Lc_opt) greater than unity, indicating the presence of large-sized specimens in the populations. Two species faced intense fishing pressure in the Atlantic while one stock collapsed in the Pacific Ocean. Our results indicate that even non-targeted pelagic can be prone to over-exploitation. Therefore, there is an urgent need for stakeholders and fisheries managers to focus on improving fishery statistics and to conduct periodic monitoring of stock status indicators for non-target species.